Manifestations of Nannies' Language in Everyday Communication between Mother and Child: Pedagogical Aspect - Anita Famuła-Jurczak (Vasyl Stefanyk Precarpathian National University, 2024)
The article substantiates the importance of nannies' language for the children's development, namely the danger of long-term use of the phonetic, morphological and syntactic properties of babysitters' language in the process of communicating with the child. The theoretical positions that are the basis for the analysis of the collected research material are related to the theories of symbolic interactionism, constructivism, and the ecological theory of human development. In the research it is assumed that the child's development is dynamic and occurs as a result of structuring and restructuring the experience gained during interaction. It is confirmed that development takes place in a certain environment, but it is worth remembering that the child is not a passive imitator of the stimuli, but as a result of mutual interaction with the environment. The child begins to form one's own image of the surrounding world. It has been found that language serves as one of the elements that allow a person to build an idea of the surrounding reality in mind. The article emphasizes the importance of speech and, more broadly, communicative competences for a child's development. The results of a study conducted among mothers of two- to three-year-old children are presented. Considering this stage of the child's development is considered special because of the phase of the child's speech development, as well as the formation of personality. The study presents a diagnostic survey and includes free communication between mother and child. The paper outlines the characteristic properties of the language of nannies. Based on the results of the study, the consequences for the development of long-term use of nanny's language by adults are shown. The article emphasizes the importance and influence of the communication skills and abilities of babysitters and parents on the child's development and further education, as well as the importance of pedagogical support for effective communication in early childhood.